PENGARUH MODEL PEMBELAJARAN GALLERY WALK TERHADAP HASIL BELAJAR KOMPONEN SISTEM AC - Romadhona Al Mustakim; Debora; Wiyogo (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2019)
This study is entitled the influence of the Walking Gallery learning model on student learning outcomes of the class XI TKR SMK Karsa Mulya Palangka Raya. Quantitative research used in this study is the Pre-experimental Design method or is an actual experiment. The data analysis technique used in this study is the data normality test proceed with homogeneous test data and the final test is the hypothesis testing data The results of the parametric hypothesis test using the t-test two correlated samples obtained the value of t_count > t_table (7.72 > 2.04). Because t_count = 7.72 is greater than t_table = 2.04, this means that H0 is rejected and H1 is accepted, which means that the Gallery learning model runs against student learning outcomes in component system lesson in class XI TKR SMK Karsa Mulya Palangka Raya runs better than student learning outcomes before learning with the gallery walk learning model